Biosurfactant production by Pseudomonas aeruginosa isolated from aquaculture farm soil and its optimisation - Nadella, Ranjit kumar; Vaiyapuri, Murugadas; kusunur, Ahamed Basha; Joseph, Toms Cheriath; Velayudhan, Lalitha Kuttanappilly; Mothadaka, Mukteswar Prasad (Indian Journal of Fisheries, 2018)
In the present study, aquaculture farm soil was screened for the biosurfactant producing bacteria. Total of 43 distinct morphological colonies were isolated from the farm soil and their biosurfactant production was evaluated by employing different screening methods. Fourteen biosurfactant producing bacterial isolates were selected based on the formation of dark blue halos on CTAB agar, emulsification index, oil spreading assay and BATH assay. Based on the results, bacterial isolate (BHA 9) showed highest production of biosurfactant and selected for further studies. Biochemical characterisation revealed that the bacterial isolate responsible for biosurfactant production is Gram negative, slender long rod shape bacteria and oxidase and catalase positive. Molecular characterisation of 16S r-DNArevealed that it belongs to Pseudomonas aeruginosa. Optimization studies were carried out at different temperatures (25, 30, 35 and 40oC) using four different carbon sources (1%) i.e., glucose, sucrose, maltose and starch and four nitrogen sources (1%) viz., peptone, ammonium nitrate, beef extract and yeast extract at different pH (6, 7, 8, 9 and 10) and NaCl levels (0.50, 1, 1.50 and 2%). Emulsification index and the bacterial biomass (OD600) were recorded at 24, 48, 72 and 96 h intervals. Optimum condition for biosurfactant production by this bacterium was achieved when glucose and yeast extract was used as carbÃ³n and nitrogen sources, respectivelyÂ  maintaining a temperature of 35oC, pH 8 and NaCl 1.5% measured in terms of emulsification index and bacterial biomass. This is the first reported study for the biosurfactant producing bacteria from aquaculture farm soil which may find its application in various fields.Â